EPISTEMOLOGI TAFSIR MAQASIDI - Kusmana, Kusmana (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This article examines tafsîr maqâṣidî in epistemological outlook. It studies the origins, methodology, and validation of its construction. Based on depth literary analysis, this article argues that tafsîr maqâṣidî cannot be separated from its origins in the historical development of Islamic law. It can be seen from the rise of tafsîr maqâṣidî that is much more originated and established from maqâṣid al-sharî’ah in terms of Islamic law. The basic framework of tafsîr maqâṣidî is not only developed by Muslim scholars who are well educated in Islamic law such as Ibn ‘Âshûr and Jaser Auda, but also initiated by scholars of theology such like Muḥammad ‘Abduh and Muḥammad Rashîd Riḍâ. The article also suggests that the movement of maqâṣid al-sharî’ah thoughts including tafsîr maqâṣidî has relevant effort in constructing Islamic knowledge which is well known in contemporary Islamic discourse as islamization of knowledge. On the origins, tafsîr maqâṣidî is like tafsir bi al-ra’y that attempts to find a logical basis and methods that is appropriate to Islamic sources, and on the same time it tries to put a logic and reason as the basis for interpretation. On methodological side, tafsîr maqâṣidî is built in two traces of tafsir tradition that is well known as naqlî and ‘aqlî methods. And on validation, tafsîr maqâṣidî forms itself into a wide creativity in using naqlî and ‘aqlî methods by emphasizing on rational and empirical study with special reference to maṣâliḥ mursalah.